2009
DOI: 10.1111/j.1574-6968.2009.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis ofXanthomonas campestrispv.campestrisin the interaction with the susceptible and the resistant cultivars ofBrassica oleracea

Abstract: Black rot of cruciferous plants, caused by Xanthomonas campestris pv. campestris, causes severe losses in agriculture around the world. This disease affects several cultures, including cabbage and broccoli, among others. Proteome studies of this bacterium have been reported; however, most of them were performed using the bacterium grown under culture media conditions. Recently, we have analyzed the proteome of X. campestris pv. campestris during the interaction with the susceptible cultivar of Brassica olerace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
4
22
0
3
Order By: Relevance
“…proteomic analysis of Xanthomonas campestris pv. campestris during its interaction with the host plant in vivo (Andrade et al ., ; Villeth et al ., ). It is clear that differences are certain to occur between bacterial interactions with the host plant in vitro and in vivo , with many processes occurring in vivo that would not occur in vitro , e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…proteomic analysis of Xanthomonas campestris pv. campestris during its interaction with the host plant in vivo (Andrade et al ., ; Villeth et al ., ). It is clear that differences are certain to occur between bacterial interactions with the host plant in vitro and in vivo , with many processes occurring in vivo that would not occur in vitro , e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide masses obtained were employed for identification with the MASCOT program (Matrix Science, London, UK) using the National Center for Biotechnology Information (NCBI) and Pfam (http://pfam.sanger.ac.uk/), and only the matches to Pectobacterium species were considered as positive identifications. Peptide sequences obtained by de novo sequencing were analysed using blast (Mattinen et al ., ; Shevchenko et al ., ; Villeth et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…CAO, that converts chlorophyll a to chlorophyll b, regulates the stabilization of light-harvesting chlorophyll a/b proteins [26]. Villeth et al [27] reported that pathogen infection could decrease the accumulation of PSII stability/assembly factor HCF136, which is important for the accurate assembly of PSII. In this study, AR remarkably decreased the abundance of CAO and PSII stability/assembly factor HCF136 in L. formosana , but no light reaction-related proteins was depressed by AR in S. superba (Table 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Such approach gives valuable information on how a bacterial pathogen adapts its gene expression pattern to the plant environment. Concerning Xcc , responses to its host plant were first reported using proteome analyses (Andrade et al ., ; Villeth et al ., ). When infiltrated inside young cabbage leaves, several proteins related to polysaccharide synthesis, resistance to oxidative stress and outer membrane proteins were found to accumulate in Xcc .…”
Section: Introductionmentioning
confidence: 97%